DEBT POLICY AS CORPORATE GOVERNANCE MECHANISM IN CONCENTRATED OWNERSHIP - ., Mutamimah (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2007)
This research aims to test the debt policy as a mechanism to reduce agency conflict among majority and minority shareholders. This test aims to answer the problems to what extend debt can be used as corporate governance mechanism in a sense of reducing agency conflict. This research is important since most of company ownership structure in Indonesia is categorized concentrated structure, where its make a conflict between majority and minority shareholders. The populations of the research are companies that go public in the Indonesian capital market until the year of 2003. These samples of this research consist of 40 companies that are selected based on nonprobability technique with purposive sampling method. They were divided into two groups, high concentrated ownership structure and low concentrated ownership structure. In processes testing the hypothesis, 2 indicators were used, i.e. market indicator and accounting indicator. Event study analysis was used for market indicator, whereas multiple regression analysis was used for accounting indicator. Based on empirical examination result, it is generally concluded that debt policy cannot be used as mechanism to reduce agency conflict among majority and minority shareholders, both at high and low concentrated ownership structure. This is because of average company debt are higher than average industry debt. Debt policy tend be used as a tool of expropriation to minority shareholders. The expropriation is higher at high concentrated ownership structure rather than at low concentrated ownership structure and the difference is significant.